HUBUNGAN KAUSALITAS ANTARA PENGELUARAN PENDIDIKAN DAN JUMLAH PENDUDUK YANG BERSEKOLAH FORMAL DI KABUPATEN ACEH BARAT - Yasrizal Yasrizal; Mahrizal Mahrizal (Universitas Teuku Umar, 2018)
This study aims to determine the relationship between government expenditure in the education sector on the number of people who attend formal schools in West Aceh Regency in the period 2005-2015. The model used is the Vector Autoregressive (VAR) model to see if there is a causality relationship between the education expenditure variable and the number of school students in West Aceh. Based on the Granger Causality Test on the two variables namely education expenditure and number of schools shows that there is no causality relationship between the two variables during the period 2005 to 2015. This is because many other factors influence government expenditure and the number of schools both government policy variables that do not looking at the number of schools, the problem of budget compliance in allocating education costs as much as 20 to the influence of budget politics. The influence of the education budget in the short term sometimes increases also decreases its influence unstable every period sometimes negative as well as the number of schools each periodKeywords: Education Expenditures, Number of School Students and Vector Autoregressive (VAR)